Pelatihan manajemen koperasi syariah sebagai upaya ‎peningkatan ekonomi masyarakat Desa Gedogkulon ‎Kabupaten Malang - Malikh, Majda Qudsiyatul (Maliki Interdisciplinary Journal, 2023)
Sharia Cooperatives are part of Islamic financial institutions that called by (LKS) which practice Islamic economic principles and aim to improve people’s welfare by focusing on the benefits and benefits of both parties involved. So the existence of sharia cooperatives in rural areas is so important in increasing the economic level of society. The people of Gedogkulon Village, which is located in Turen District, Malang Regency, East Java Province, are currently still having difficulties with the financial administration system. At MSME locations there is only a place for production, there is no place for administration, thus hindering the recording system for evidence of economic activity. Besides that, in Gedog Kulon village there is no cooperative that helps residents in improving their welfare. This has become an urgency to provide education for Gedogkulon villagers about the concept, mechanism and mission of the Islamic economy through the implementation of sharia cooperatives. The results of the training prove that there is an increased understanding of the ranks of village officials and the community about sharia cooperatives with the contribution and cooperation of all village communities. The people of Gedogkulon village want to implement and immediately revive cooperatives that have existed in the sharia version. Based on the participation of the village community and cooperative administrators in Gedogkulon village, it is hoped that the results of this training can make a major contribution to the development of the village itself.